Endocannabinoid System as Therapeutic Target of PTSD: A Systematic Review - Steardo, Luca (Life (Basel), 2021)
Post-Traumatic Stress Disorder (PTSD) is a complex disorder involving dysregulation of stress-related hormones and neurotransmitter systems. Research focused on the endocannabinoid system (eCBS) for anxiety and stress regulation, cognitive and emotional responses modulation and aversive memories extinction, leading to the hypothesis that it could represent a possible alternative treatment target for PTSD. In this systematic review, we summarize evidence about the efficacy and safety of medicinal cannabidiol (CBD), Δ(9)-tetrahydrocannabinol (Δ(9)-THC), and nabilone in PTSD treatment. The PRISMA statement guidelines were followed. A systematic literature search was conducted in MEDLINE/PubMed, Scopus and Web of Science by two independent researchers, who also performed data extraction and quality assessment. Among the initial 495 papers, 234 were screened for eligibility and 10 were included. Studies suggested that different medicinal cannabinoids at distinct doses and formulations could represent promising treatment strategies for the improvement of overall PTSD symptomatology as well as specific symptom domains (e.g., sleep disorders, arousal disturbances, suicidal thoughts), also influencing quality of life, pain and social impact. Although there is a robust rationale for treatment with drugs that target the eCBS and the results are promising, further studies are needed to investigate the safety and efficacy profile of their prolonged use.